Political Trust and Values of Loyal and Oppositional Youth in the Exclave Region of Russia - Aleksandr V. Shchekoturov (Peoples’ Friendship University of Russia (RUDN University), 2021)
The study determines the level of trust in public and political institutions among the loyal and oppositional youth of the Kaliningrad region, as well as their attitudes towards materialistic and post-materialistic values. The study is based on R. Ingleharts theory of value and the understanding of trust as described in the works of P. Sztompka and A. Giddens. The author relies on an online survey conducted among young people aged between 18 and 35 (n = 987). As a result of the study, the author defines three groups of institutions, depending on the degree of trust in them. The study confirms the hypothesis that young people loyal to the government demonstrate greater trust in traditional and state institutions. It also reveals that, in general, young people put post-materialistic values in the first place, while materialistic values are more characteristic of the youth loyal to the government. The author concludes that the level of the political trust towards a certain institution among loyal and oppositional youth differs depending on the possibility of influencing the institution. The trust of loyal youth is based on the importance of social status, and the trust of oppositional youth is based on the freedom of expression.